Hypertriglyceridemia induced acute pancreatitis in pregnancy: Learning experiences and challenges of a Case report - Athar, Sufia; Ramawat, Joohi; Aziz, Mohammad Abdel; Boama, Vincent (Clinical Journal of Obstetrics and Gynecology, 2019)
Hyperglyceridemia induced pancreatitis in pregnancy accounts for 4% of all cases of acute pancreatitis. Though rare, hypertriglyceridemia induced pancreatitis may lead to fatal maternal and fetal complications, even maternal death. Its management during pregnancy remains a challenge for many physicians. Management options are limited in pregnancy. In the refractory cases, management options and timing of delivery is debatable. Here we report a case of hyperglyceridemia induced pancreatitis and the challenges faced in the management.